(untitled) (Revista Latino-Americana de Enfermagem, 2006)
This qualitative study shows the results of workshops held with health workers and public health users (raped women), aimed at raising these women's self-esteem and creating awareness among health workers who attend them. Neuro-Linguistic Programming techniques were used to bring back life experiences, which contributed to a re-reading and to minimize causal factors of low self-esteem. Themes like repugnance, fear and the fruit of rape; image and place; death; revenge; support and solidarity; domestic violence and bad care delivery to victims were addressed during the meetings. The stories were transcribed and analyzed, preserving content fidelity. Experiences lived at home and with loved and admired people, and mainly experiences resulting from the rape were responsible for the low self-esteem. The evaluations indicated the workshops as an opportunity to reflect, to return to normal life and to reconstruct self-esteem, for the raped women as well for the health workers who deliver care to them.